Use of exercises with increased coordination complexity in the training process of young female volleyball players aged 13-14 years - Roman Boichuk; Sergii Iermakov; Mykola Nosko; Yuliya Nosko; Ivan Vaskan; Mykhailo Коrop; Halyna Kurtova; Zhanna Grashchenkova (IP Iermakov S.S., 2023)
Background and Study Aim. In the context of training young female volleyball players, understanding the criteria, extent, and impact of exercises with heightened coordination complexity becomes crucial. This study aims to determine the evaluation criteria, scope, and effects of incorporating exercises with elevated coordination demands on the specific athletic readiness of young female volleyball players aged 13-14 years. Material and Methods. The study involved female volleyball players aged 13-14 years (n=24) with an average of 4 years of professional experience. Participants were divided into a control group (n=12) and an experimental group (n=12). Prior to the study, both children and their parents were thoroughly informed about the research procedures, and parental consent was obtained for participation. The coordination exercises were categorized into five groups, each assigned a complexity rating from 1 to 5. The assessment utilized a battery of tests. Results. The findings reveal that coordination training yielded a more pronounced advancement in the development of various coordination abilities among female volleyball players in the experimental group, as compared to those in the control group. A statistically significant enhancement (p<0.05) was evident across all indices of coordination readiness within the experimental group. In contrast, the control group demonstrated notable progress only in 3 out of 10 instances (p<0.05). In the control group, noteworthy increases (p<0.05) were observed in spatial orientation, motor activity restructuring, and response indicators. Female volleyball players in the experimental group exhibited substantial improvement (p<0.05-0.001) across all indicators of technical readiness, including reception, attack hit, serve, and ball pass. Conversely, the control group players showed comparatively less remarkable changes in this aspect of readiness, with significant enhancement (p<0.05) identified in three parameters. Conclusions. The strategic incorporation of exercises with progressively heightened coordination demands emerges as a valuable approach in substantially enhancing the range of coordination abilities among young female volleyball players. Recognizing this factor provides the means to expedite and optimize the mastery of motor skills more effectively.